Frequent Detection of Noroviruses and Sapoviruses in Swine and High Genetic Diversity of Porcine Sapovirus in Japan during Fiscal Year 2008 - Nakamura, Kazuya (American Society for Microbiology (ASM), 2010)
A molecular biological survey on porcine norovirus (NoV) and sapovirus (SaV) was conducted in Toyama Prefecture, Japan, during fiscal year 2008. Both NoV and SaV were detected from swine fecal samples throughout the surveillance period, indicating that these viruses were circulating in this region. NoV strains detected in this study belonged to three genotypes that are known as typical swine NoVs. Although human NoVs were occasionally detected, it was unclear whether they replicated in pigs. As for SaV, genogroup VII (GVII) and other divergent genogroups were identified in addition to the dominant genogroup, GIII, which is the prototypic porcine SaV. In addition, 3 strains genetically related to human SaV were detected. Two of these 3 strains were closely related to human SaV GV. Our study showed that genetic diversification of porcine SaV is currently progressing in the swine population.